2003
DOI: 10.1161/01.cir.0000054623.35669.3f
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 Protects Against the Development of Cardiac Allograft Arteriosclerosis

Abstract: Background— Angiopoietin (Ang)–1 is an angiogenic growth factor that counteracts the permeability and proinflammatory effects of vascular endothelial growth factor and other proinflammatory cytokines. Recently, we demonstrated that vascular endothelial growth factor enhances cardiac allograft arteriosclerosis. Here, we studied the roles of Ang1, its natural antagonist Ang2, and their receptor Tie2 in rat cardiac allograft arteriosclerosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 31 publications
4
68
0
Order By: Relevance
“…Recently, Ang1 was also reported to protect vessels against the development of arteriosclerosis in cardiac allografts. 31 Edema and inflammation were also reported in the rabbit skeletal muscles after VEGF-A gene therapy. 32 In an earlier study by our group, delivery of the AdvVEGF-A into the periadventitial space of the carotid arteries resulted in a significant increase in inflammatory infiltrates 15 as compared to the controls.…”
Section: Angiopoietin Gene Transfer To Vascular Tissue S Bhardwaj Et Almentioning
confidence: 95%
“…Recently, Ang1 was also reported to protect vessels against the development of arteriosclerosis in cardiac allografts. 31 Edema and inflammation were also reported in the rabbit skeletal muscles after VEGF-A gene therapy. 32 In an earlier study by our group, delivery of the AdvVEGF-A into the periadventitial space of the carotid arteries resulted in a significant increase in inflammatory infiltrates 15 as compared to the controls.…”
Section: Angiopoietin Gene Transfer To Vascular Tissue S Bhardwaj Et Almentioning
confidence: 95%
“…Their previous work 14 showed that vascular endothelial growth factor (VEGF) enhanced formation of these lesions. In their current article, 13 they show that its endogenous antagonist, angiopoietin-1, can forestall lesion formation. These observations draw attention to the role of microvessels in this disease.…”
Section: See P 1308mentioning
confidence: 80%
“…Later studies showed that during the allogeneic response in vitro, T lymphocytes produce angiogenic growth factors including VEGF. 17,18 Thus, the observations of Nykänen et al 13 may have particular relevance to this special form of arteriosclerosis. In addition to angiopoietin, transplanted hearts can overexpress another endogenous modulator of angiogenesis.…”
Section: See P 1308mentioning
confidence: 94%
See 2 more Smart Citations